ICT - USE OF DIGITAL TECHNOLOGIES IN HIGHER EDUCATION: from possibilities and innovations to overcoming barriers and challenges - Paulista, Cristian Augusto; Alves, Renato dos Santos (Revista Interface Tecnológica, 2022)
Digital information and communication technology (ICT) is increasingly integrated into our daily lives, in all aspects and environments, bringing great challenges and changes to contemporary society. The introduction of digital technologies in higher education brings great benefits for educators, students, and the academic field in general. However, for the integration of ICTs to bring about changes in the university environment, it is necessary to understand the possibilities, obstacles, challenges and trends necessary for such integration. Therefore, the objective of this paper is to evaluate by means of literature review using multiple databases, the use of digital technologies in higher education, its challenges and overcoming. However, it was noticed that the insertion of digital technology in the Brazilian university environment is still very slow. And such slowness occurs due to the lack of investments in infrastructure and necessary digital equipment, the possibilities of these technologies, and the understanding of this integrated teacher training